THE USE OF 3H (HERE, HIDDEN, IN MY HEAD) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Revi Oktarina (Language and Education Journal, 2017)
Reading is very crucial for students to be learned in order to achieve success. However, students still find difficulties in comprehending reading narrative text. The objective of this study was to find out whether or not there was a significant difference in reading comprehension achievement between the eighth graders of SMP Negeri 4 Kayuagung who were taught by using 3H (Here, Hidden, in my Head) strategy and that of those who were not. The quasi-experimental method was used in this study. The samples of the study were 60 students of the eighth graders of SMP Negeri 4 Kayuagung taken by purposive sampling method. Based on the result of independent sample t-test, it was found that t-obtained (9.39) was higher than t table (2.00) and pvalue (0.00) was less than ɑvalue (0.05). It showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It meant that there was a significant difference in reading comprehension achievement between the students who were taught by using 3H (Here, Hidden, in my Head) strategy and that of those who were not. In order words, 3H (Here, Hidden, in my Head) strategy could improve students’ reading comprehension achievement in eighth graders of SMP Negeri 4 Kayuagung